PERUBAHAN IKLIM: DAMPAKNYA TERHADAP PRODUKTIVITAS MANGGA DI KABUPATEN CIREBON DAN STRATEGI PENANGULANGANYA OLEH PETANI - Rasmikayati, Elly; Trimo, Lucyana; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Mango is a fruit whose production level has great potential in Cirebon Regency in its improvement and development. Mango production often declines due to uncertain climatic conditions. The phenomenon of climate change that requires a long time to investigate and will continue for a long period of time. The purpose of this study was (i) to determine the description of mango production in Kab. Cirebon, (ii) to determine the effect of climate change on mango production in Kab. Cirebon, and (iii) to find out farmers' strategies in dealing with climate change. The design of this research is a qualitative survey method and the analytical tools used are descriptive statistics and statistical analysis of the average difference test. The results of the study showed that the average mango production before climate change and after climate change decreased. Mango production before and after climate change on land area < 0.5 Ha and 0.5-1 Ha showed a significant difference, while in land area > 1 Ha, there was no significant difference. The strategies used by farmers are the use of drugs, sanitation, ditch construction, and attending SLPHT schools.